2010
DOI: 10.1242/jeb.043414
|View full text |Cite
|
Sign up to set email alerts
|

Application of the two-sample doubly labelled water method alters behaviour and affects estimates of energy expenditure in black-legged kittiwakes

Abstract: SUMMARYDespite the widespread use of the doubly labelled water (DLW) method in energetic studies of free-ranging animals, effects of the method on study animals are rarely assessed. We studied behavioural effects of two alternative DLW protocols. During two consecutive breeding seasons, 42 parent black-legged kittiwakes received either the commonly used two-sample (TS) or the less invasive single-sample (SS) DLW treatment. A third group served as a non-treated control. We evaluated the effect of treatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…Given that extensive restraint alters birds' behaviour, and consequently daily energy expenditure (Schultner et al, 2010;Hinsley et al, 2011), we attempted a modified two-sample technique. To reduce disturbance and associated possibility of abandonment with a costly accelerometer attached, we injected the DLW intravenously and our second sample was taken only 12 min after injection to reduce the impact of extended restraint on behaviour.…”
Section: Doubly Labelled Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Given that extensive restraint alters birds' behaviour, and consequently daily energy expenditure (Schultner et al, 2010;Hinsley et al, 2011), we attempted a modified two-sample technique. To reduce disturbance and associated possibility of abandonment with a costly accelerometer attached, we injected the DLW intravenously and our second sample was taken only 12 min after injection to reduce the impact of extended restraint on behaviour.…”
Section: Doubly Labelled Watermentioning
confidence: 99%
“…Daily energy expenditure has seldom been reported in the order Suliformes (Shaffer, 2011; referred to there as 'Pelecaniformes' from which Suliformes has recently been split), only once in cormorants (Keller and Visser, 1999), and never in a small cormorant species, presumably because many cormorants are very sensitive to disturbance. The two-sample DLW method requires holding large animals for over an hour, and that lengthy period of restraint can cause abandonment of offspring or altered behaviour (Schultner et al, 2010;Hinsley et al, 2011). Obtaining direct estimations of daily energy expenditure would be useful for validating estimates from bioenergetic models used to quantify the impact of cormorants on fisheries (Ridgway, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The practical difficulties (and costs) of the use of DLW in free-living animals has undoubtedly contributed to problems with small sample sizes, and hence low statistical power, in assessments of behavioural effects (Zurowski & Brigham 1994, Wilson & Culik 1995. The recent study by Schultner et al (2010) was designed to address these problems and showed an effect of the two-sample procedure on both behaviour and estimates of energy expenditure in Black-legged Kittiwakes. The authors suggested that the initial period of restraint required for equilibration by this method may have been a major factor, acting through stress and/or by increasing time required for plumage maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…Whatever the mechanism, an effect of stress seems likely in that Schultner et al (2010) found stronger negative effects in a year of unfavourable foraging conditions; thus the Kittiwakes may have had less tolerance to the stress imposed by the procedure during a year when environmental stress was already high. Experience from our work with both Great Tits and Blue Tits using a two-sample DLW method concurs with this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation